Analysis of Arabic Teaching Books Class X with Praxeology Approach - Shofa Musthofa Khalid; Hikmah Maulani; Nalahuddin Saleh; Muhammad Faris Imaduddin; Eneng Komariyah Maimun RNM; Ijlal Haziel Taufik (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
This study aims to determine whether the material for specialization Arabic textbooks published by the Directorate KSKK the Ministry of Religion Affairs is interactive and can be used for high school level students and their relevance to student abilities. The research method used in this research is a qualitative-descriptive method with a literature study design. There is two technique collection; primary sources in the form of Arabic textbooks for class X published by the Directorate KSKK the Ministry of Religion Affairs, and secondary sources in the form of books and journals relevant to related topics. From the results of the analysis carried out, it was concluded that this book was not deemed feasible and suitable for use by students as teaching materials that could support the achievement of the objectives of learning Arabic, both in terms of theory and practice. So it is necessary to make improvements, in terms of content. Hopefully, these findings can become a reference and have positive implications in correcting existing deficiencies.